2015
DOI: 10.1007/s00423-015-1290-2
|View full text |Cite
|
Sign up to set email alerts
|

Low serum factor V level: early predictor of allograft failure and death following liver transplantation

Abstract: Assessment of serum factor V levels on postoperative day 2 might be a promising prognostic tool for early prediction of inferior outcomes after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Factor V has been more extensively studied in non-trauma situations, including liver transplantation and shock. Zulian et al found factor V serves as an early predictor of allograft failure and death in liver transplant patients(21). Additionally, the PROWESS trial found heterozygous factor V leiden carriers displayed reduced mortality in the setting of sepsis(22).…”
Section: Discussionmentioning
confidence: 99%
“…Factor V has been more extensively studied in non-trauma situations, including liver transplantation and shock. Zulian et al found factor V serves as an early predictor of allograft failure and death in liver transplant patients(21). Additionally, the PROWESS trial found heterozygous factor V leiden carriers displayed reduced mortality in the setting of sepsis(22).…”
Section: Discussionmentioning
confidence: 99%
“…Low coagulation factor synthesis and coagulopathy represent the earliest signs of liver dysfunction. Low levels of factor V seem to be early predictors (day 2) of allograft failure [8]. ROTEM assay, as a viscoelastic test, may represent a superior method of detection decreased coagulation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation disorders represent one of the most early and specific signs for initial graft poor function (IGPF) [8,9]. Based on this assumption, the aim of our study was to evaluate if coagulation kinetics, as assessed by rotational thormoboelastometry (ROTEM) 24 hours after LT, can be used in the early diagnosis of EAD.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the basis for the fact that the plasma half-life of factor V is relatively short, about 12-24 hours, and a decrease in factor V is the most sensitive indicator of liver failure [14,15]. Many studies also suggest that factor V levels are related to survival and can serve as a prognostic indicator [16][17][18]. Interestingly, the gene for factor V related to the family of multi-copper oxidases, and is homologous to coagulation factor VIII.…”
Section: Discussionmentioning
confidence: 99%